2004
DOI: 10.1071/ea02054
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of beef cattle breeding schemes incorporating performance testing of young bulls for feed intake

Abstract: A model beef cattle breeding scheme consisting of a breeding unit and a commercial unit was used to evaluate the impact on genetic gain and profitability of incorporating feed intake measurements as an additional selection criterion in breeding programmes. Costs incurred by the breeding unit were compared with returns generated in the commercial unit, with bulls from the breeding unit being used as sires in the commercial unit. Two different market objectives were considered — a grass-fed product for the Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…There were no statistically significant differences in RFI between the lamb genotypes, and for each lamb genotype a considerable range in RFI was found (Blackface, 20.33 to 10.19; Swaledale cross, 20.25 to 10.24; Cheviot cross, 20.30 to 10.21; Lleyn cross, 20.31 to 10.24; Texel cross, 20.20 to 10.19 kg DM/day). Archer et al (2004) concluded that profit was maximised when RFI measurement was included in beef cattle breeding schemes for the top 10% to 20% performance tested bulls. There may be scope for inclusion of (residual) feed intake into the selection objectives of terminal sire breeds to increase growth rate without increasing feed intake (Cammack et al, 2005).…”
Section: Table 9amentioning
confidence: 99%
“…There were no statistically significant differences in RFI between the lamb genotypes, and for each lamb genotype a considerable range in RFI was found (Blackface, 20.33 to 10.19; Swaledale cross, 20.25 to 10.24; Cheviot cross, 20.30 to 10.21; Lleyn cross, 20.31 to 10.24; Texel cross, 20.20 to 10.19 kg DM/day). Archer et al (2004) concluded that profit was maximised when RFI measurement was included in beef cattle breeding schemes for the top 10% to 20% performance tested bulls. There may be scope for inclusion of (residual) feed intake into the selection objectives of terminal sire breeds to increase growth rate without increasing feed intake (Cammack et al, 2005).…”
Section: Table 9amentioning
confidence: 99%
“…These costs may be between 70 and 80% of the total costs of the breeding unit (Archer et al, 2004). Several authors have demonstrated the importance of RFI for decreasing these costs.…”
Section: Resultsmentioning
confidence: 99%
“…First there needs to be a major emphasis on reducing inputs both to ease pressure caused by competition for the cropland used to produce grain for human consumption and biofuel production but also to reduce the breakeven point for producers. Improving feed efficiency could improve long-term profitability for beef producers by as much as thirty-three percent [14]. However, to accomplish this, the molecular basis for feed efficiency needs to be established both in soft tissues of the carcass and in regions of the brain known to regulate satiety, metabolic rate and modulation of the somatotropic axis.…”
Section: Research Priorities Needed To Enhance Sustainable Beef Produmentioning
confidence: 99%